Thermitic thermodynamics : a computational survey and comprehensive interpretation of over 800 combinations of metals, metalloids, and oxides - Shaw, Anthony Peter Gordon (Boca Raton : CRC Press, 2020)
"Thermites, generally considered to be mixtures of metals and metal oxides, are an important subset of energetic materials. Describing the results of calculations on 800 possible combinations of metal and metal oxide reactants, this practical overview will serve those in energetic materials, pyrometallurgy, chemistry, and materials science"--
An introduction to thermitic reactivity -- Characteristics of the metal-metal oxide reaction matrix -- Some thermodynamic concepts and considerations -- Applying thermodynamic concepts -- Additional topics -- Magnesium-oxidizer systems -- Titanium-oxidizer systems -- Zirconium-oxidizer systems -- Hafnium-oxidizer systems -- Vanadium-oxidizer systems -- Niobium-oxidizer systems -- Tantalum-oxidizer systems -- Chromium-oxidizer systems -- Molybdenum-oxidizer systems -- Tungsten-oxidizer systems -- Manganese-oxidizer systems -- Iron-oxidizer systems -- Cobalt-oxidizer systems -- Nickel-oxidizer systems -- Copper-oxidizer systems -- Zinc-oxidizer systems -- Cadmium-oxidizer systems -- Boron-oxidizer systems -- Aluminum-oxidizer systems -- Silicon-oxidizer systems -- Tin-oxidizer systems -- Lead-oxidizer systems -- Antimony-oxidizer systems -- Bismuth-oxidizer systems -- Systems involving group 3 and lanthanide elements -- Systems involving actinide elements -- Metal-boron systems and Ti-B4C, Ti-C -- Metal-silicon systems -- Intermetallic systems.
OCLC-licensed vendor bibliographic record.
Keywords: Thermochemistry; Thermit; Metallic oxides; Pyrometallurgy; Powder metallurgy; Oxidizing agents; SCIENCE / Chemistry / General; SCIENCE / Chemistry / Analytic; SCIENCE / Chemistry / Industrial & Technical